Surgical Outcomes of Rhegmatogenous Retinal Detachment with Different Peripheral Vitreous-Shaving Procedures - Nishitsuka, Koichi (Clin Ophthalmol, 2021)
PURPOSE: To compare the surgical outcomes of vitreous surgery for rhegmatogenous retinal detachment (RRD) after two different peripheral vitreous-shaving techniques are performed. METHODS: We reviewed 269 eyes with RRD that were treated with a 25-gauge vitrectomy by a single surgeon between June 2015 and May 2020. The exclusion criteria for the proposed air tamponade selection were as follows: more than two weeks since RRD onset, giant retinal tears, a history of complications following cataract surgery, high myopia, and proliferative vitreoretinopathy classified as grade C or higher. We examined the differences in the therapeutic effect between shaving under slit lamp microscope illumination (group A) and shaving under a wide-angle viewing system (group B). RESULTS: A total of 269 eyes were included in this study, with 146 eyes in group A and 123 eyes in group B. The primary anatomical success rates did not differ between group A (97.3%; 142/146 eyes) and group B (97.6%; 120/123 eyes; P = 0.102). However, the surgical time was significantly longer in group A (60.2 ± 17.1 min) than that in group B (46.9 ± 12.6 min) (P < 0.001). The multiple linear regression analysis revealed that surgical time was significantly correlated with using the wide-angle noncontact viewing system for vitreous shaving (adjusted R(2) = 0.248; beta [standard partial regression coefficient] = −0.447, P < 0.001), the number of retinal breaks (beta = 0.182, P = 0.001), and the quadrant of retinal detachment (beta = 0.205, P < 0.001). CONCLUSION: The surgical outcomes were similar regardless of the shaving procedure performed, and the surgical time was shortened by using the wide-angle noncontact viewing system for vitreous shaving.